Case Report: Next-Generation Sequencing Reveals Tumor Origin in a Female Patient With Brain Metastases - Li, Qun; Zhang, Xiaoyan; Feng, Jiao; Cheng, Dezhi; Cai, Lin; Dai, Zhang’an; Zhao, Shuyu; Li, Jianmin; Huang, Jingjing; Fang, Yu; Zhu, Honglin; Wang, Danhua; et al. (Frontiers in Oncology, 2021)
Background Brain metastasis mainly originates from lung cancer. Napsin A and TTF-1 factors have frequently been detected in lung adenocarcinoma cases. Brain metastasis tumors with napsin A and TTF-1 positive are easily classified as lung adenocarcinoma origin. However, some thyroid cancers also exhibit these clinical features. Besides, lung is the most common metastasis of undifferential thyroid cancer. Therefore, it requires development of novel diagnostic tools to aid in distinguishing between pulmonary and thyroid origin. Patient Findings We reported a case that was initially diagnosed as brain metastatic lung cancer based on immunohistochemistry results. Analysis of next-generation sequencing (NGS) data from the brain lesion revealed that the cancer may have originated from the thyroid. We detected combo mutations in TERT promoter mutation, RET fusion and TP53, which are common in undifferential thyroid cancer (UTC), but rare for lung cancer. These results, coupled with identification of PAX8, indicated that this patient had UTC. Additionally, her three sons, despite being asymptomatic, were all diagnosed with papillary thyroid carcinoma. Summary The patient received anlotinib treatment and showed good clinical outcomes. One month after anlotinib treatment, the pulmonary nodules were found to be controlled, and the thyroid tumor drastically reduced, and tracheal compression relieved. She continued anlotinib treatment for the following two months, but died one month later because the treatment stopped owing to financial reasons. All her sons underwent total thyroidectomy with lymph node dissection. Conclusions Although NGS has been reported to assist in diagnosis of the origin of some tumors, this is the first evidence of NGS for the determination of the origin of thyroid tumors. To our knowledge, this is the first time that a combination of multiple mutations has been used to help determine the origin of a tumor, compared with the previous single mutant gene. Moreover, this is the first evidence on the use of anlotinib for treatment of UTC with distant metastasis. Besides, all three sons of the patient had thyroid carcinoma in subsequent examinations, indicating high-risk for familial non-medullary thyroid cancer in UTC patients and necessity for performing thyroid ultrasound testing in other family members.